2019
DOI: 10.1016/j.tcb.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

RNA: Nuclear Glue for Folding the Genome

Abstract: A significant amount of RNA is present in the nucleus of mammalian cells but only a small proportion of it is destined for the cytoplasm and subsequent translation, leaving much RNA to associate with chromatin. Historically nuclear RNA was thought to interact with proteins to form a filamentous nuclear matrix, but this idea became less popular as more dynamic models of chromatin behavior became more prevalent. Using new molecular and imaging approaches it is becoming clear that RNA should be considered as an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 82 publications
4
51
0
Order By: Relevance
“…Indeed, although the compartmentalization was not markedly altered (Fig 4) we observed a reduction in TAD boundary strength upon transcriptional inhibition ( Fig 5). These results are concordant with a model where the act of transcription and or its product influences the nuclear positioning of the newly transcribed DNA locus via interaction with nuclear matrix proteins [27,28,61,62]. Lastly, the RNase A-treated cells before crosslinking display a subtle perturbation of compartmental interactions, especially in Btype compartments, even though TAD structures were preserved (Figs 2 and 3).…”
Section: Proper Tad and Genomic Compartment Formationsupporting
confidence: 87%
“…Indeed, although the compartmentalization was not markedly altered (Fig 4) we observed a reduction in TAD boundary strength upon transcriptional inhibition ( Fig 5). These results are concordant with a model where the act of transcription and or its product influences the nuclear positioning of the newly transcribed DNA locus via interaction with nuclear matrix proteins [27,28,61,62]. Lastly, the RNase A-treated cells before crosslinking display a subtle perturbation of compartmental interactions, especially in Btype compartments, even though TAD structures were preserved (Figs 2 and 3).…”
Section: Proper Tad and Genomic Compartment Formationsupporting
confidence: 87%
“…In fact, the induction of LINC00607, SERPINE1, and FN1 continued or sustained despite the removal of detrimental stimuli ( Figure S10B). These data suggest that the mechanisms involving the RNA-chromatin contacts may be an important, yet poorly elucidated, layer underlying various biological processes, as has been proposed recently 46,47 . As proof-ofprinciple, our study provides a first example of how mapping of RNA-chromatin interactomes can provide novel insights into understanding endothelial dysfunction, a dynamic and vital process preceding a variety of diseases.…”
Section: Discussionmentioning
confidence: 52%
“…Early studies revealed significant numbers of chromatin-associated RNAs (Holmes et al 1972;Kanehisa et al 1972;Bynum and Volkin 1980). The current results demonstrate that chromatin-associated RNA plays an important role in nuclear organization, chromatin folding, and transcription control (Holoch and Moazed 2015;Li and Fu 2019;Nozawa and Gilbert 2019). Long ncRNAs (lncRNAs, > 200 nt) participate 3 in various biological processes, from regulating enzymatic activities to sustaining genome imprinting and nuclear body biogenesis (Quinn and Chang 2016;Sun et al 2018).…”
Section: Introductionmentioning
confidence: 70%
“…A growing body of evidence implicates ncRNAs in spatial genome organization (Engreitz et al 2016;Li and Fu 2019;Nozawa and Gilbert 2019). Several studies suggest that enhancer RNAs (eRNA) help to juxtapose an enhancer and its target promoter (Li et al 2016).…”
Section: Introductionmentioning
confidence: 99%